Analisis Strategi Pemasaran Pada Toko Kain Kinako Kabupaten Tana Toraja - Euodia Euodia; Dina Ramba; Westerini Lusdani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this study was to find out the strategy for the Kinako Fabric in Tana Toraja district. The type of research used in this research is descriptive qualitative, namely managing information data from observation based on the facts that exist in the Kinako Fabric Shop. The types of data used are primary data and secondary data. The stategy used at the Kinako Cloth Shop is the marketing mix 4P (Product), (Price), (Promotion), (Place). Product strategy in the from of adding cloth products, Pricing strategy by providing price discounts, Promotion strategy though social media facebook and whatsapp as well as direct promotion by word of mouth, the price is quite strategic and very easy to reach potential customers. This strategy is carried out to add customers and to increase sales results.